Implementasi Layanan Konseling Individual Dalam Mengatasi Kedisiplinan Siswa Di Madrasah Aliyah An Nur Setupatok - Taruna, Azis; Herawati, Endang Sribudi; Kholiq, Abdul (Bimbingan dan Konseling, FKIP, Universitas Nahdlatul Ulama Cirebon, 2023)
Guidance and counseling teachers or school counselors have the responsibility to provide guidance and counseling services to students. Guidance is not only given to students who have problems, every student has the right to receive guidance to improve their potential or get direction about their talents and interests. Guidance and counseling teachers or school counselors are expected to be able to provide guidance and counseling programs and services. SMK Al-asy'ariyah Losari Cirebon has one linear guidance and counseling teacher, the guidance and counseling teacher plays a very important role as a motivator, and mentor for students. In addition, guidance and counseling teachers have work programs or services that are implemented in schools well to help students complete their assignments.